Izpodbojnost pravnih poslov - Polajnar-Pavčnik, Ada (Pravni letopis, 2011)
The paper deals with voidable contracts. The author presents cases where the contract is not valid due to mistake, undue inluence or lack of capacity. First the author emphasizes the theory of afirmation of contract. After that the evolution and characteristics of the phenomena of voidability (i.e. its working, the way of enforcing, the legitimate subject) are analyzed. The different standpoints of the problem how to realize the right to invalidate the contract are confronted. All the topics are highlighted with the most significant court decisions.
Keywords: civil law; izpodbojnost; liability; mistake; napake volje; neveljavnost; obligacijsko pravo; odškodninska odgovornost; pogodbe; prilagoditev; razveljavitev; to adapt; to invalidation; voidability